Interleukin-1β gene rs1143634 polymorphism and cardiovascular complications in patients with coronary artery atherosclerosis - E. V. Khazova; O. V. Bulashova; E. V. Valeeva (Евразийский Кардиологический Журнал, 2023)
The course of heart failure, regardless of its etiology, is associated with local and systemic activation of inflammatory signaling cascades. Identification of the association of candidate cytokine genes with the risk of developing coronary heart disease and chronic heart failure remains a subject of interest for many researchers. The review presents an analysis of studies of the rs1143634 polymorphism of the IL-β gene in relation to the risk of atherosclerotic cardiovascular complications. The presence of the minor allele T is associated with an increase in the concentration of IL-1β in the blood serum. Data on the role of the rs1143634 polymorphism of the IL-β gene in atherosclerotic coronary heart disease, including in combination with chronic heart failure syndrome, are presented, taking into account ethnic characteristics and gender of patients. The carriage of the T allele was associated with the risk of developing atherosclerosis and myocardial infarction. At the same time, it is reported that the C allele and the CC genotype of the rs1143634 polymorphism of the IL-1β gene were a genetic risk factor for the development and progression of heart failure. In a number of studies and meta-analyses, the association of this polymorphism with diseases of the cardiovascular system was not confirmed, but certain trajectories of the risk of complications were identified due to differences in the rs1143634 polymorphism of the IL-β gene in heart failure.